Plant-Based and Hybrid Patties with Healthy Fats and Broccoli Extract Fortification: More Balanced, Environmentally Friendly Alternative to Meat Prototypes? - Josemi G. Penalver; Maite M. Aldaya; Débora Villaño; Paloma Vírseda; Maria Jose Beriain (Foods)
Hybrid and plant-based products are an emerging trend in food science. This study aimed to develop three patty prototypes (meat, hybrid, and plant-based) enhanced with vegetable fat replacement and broccoli extract using a soy allergen-free protein matrix treated with high hydrostatic pressure (HHP) and sous vide cooking to create sustainable and nutritious burger alternatives. The samples were evaluated for microbiological safety, proximal composition, physicochemical properties, sensory characteristics, and carbon footprint. The key findings revealed that the plant-based patties had the smallest carbon footprint (0.12 kg CO2e), followed by the hybrid patties (0.87 kg CO2e) and the meat patties (1.62 kg CO2e). The hybrid patties showed increased hardness, cohesiveness, gumminess, and chewiness compared to the meat patties after sous vide treatment. This improvement likely results from synergies between the meat and plant proteins. Regarding the treatments, in all the samples, the highest hardness was observed after the combined HHP and sous vide treatment, an interesting consideration for future prototypes. Sensory analysis indicated that the plant-based and hybrid samples maintained appealing visual and odour characteristics through the treatments, while the meat patties lost the evaluator’s acceptance. Although further improvements in sensory attributes are needed, hybrid patties offer a promising balance of improved texture and intermediate carbon footprint, making them a viable alternative as sustainable, nutritious patties.